2015
DOI: 10.1088/0957-4484/26/21/215205
|View full text |Cite
|
Sign up to set email alerts
|

The electronic origin of shear-induced direct to indirect gap transition and anisotropy diminution in phosphorene

Abstract: Artificial monolayer black phosphorus, so-called phosphorene, has attracted global interest with its distinguished anisotropic, optoelectronic, and electronic properties. Here, we unraveled the shear-induced direct-to-indirect gap transition and anisotropy diminution in phosphorene based on first-principles calculations. Lattice dynamic analysis demonstrates that phosphorene can sustain up to 10% applied shear strain. The bandgap of phosphorene experiences a direct-to- indirect transition when 5% shear strain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
50
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 55 publications
10
50
0
1
Order By: Relevance
“…On the other hand, the inversion symmetry of phosphorene implies that shear cannot contribute to the electronic structure to linear order. Consistent with this, we find that the contributions to the electronic structure from an applied shear cancel to linear order, leaving the band structure unchanged for small shear [23].…”
Section: B Strained Phosphorenesupporting
confidence: 84%
“…On the other hand, the inversion symmetry of phosphorene implies that shear cannot contribute to the electronic structure to linear order. Consistent with this, we find that the contributions to the electronic structure from an applied shear cancel to linear order, leaving the band structure unchanged for small shear [23].…”
Section: B Strained Phosphorenesupporting
confidence: 84%
“…The crystallography-dependent properties of phosphorene make its electronic behavior more controllable. Recent studies reveal a high degree of anisotropic electrical and optical properties of phosphorene, which further confirm the importance of this new 2D semiconductor as a promising candidate for nano-electronic [10,14], nano-thermoelectric [15] and plasmonic applications [16,17].…”
Section: Introductionmentioning
confidence: 72%
“…One of the exciting properties of phosphorene is it's anisotropic electrical conductance and optical responses, 4 which is attributed to the anisotropy of the effective mass of the charge carriers. 7,29 As shown in Fig. 1(e), compared to the Γ-Y direction, both the valence and conduction band in the Γ-X direction are relatively flat in pristine phosphorene near the Γ point.…”
Section: Fluorination Of Phosphorenementioning
confidence: 86%
“…It has been shown that by applying strain, the electron effective mass tensor can be rotated by 90 • , taking the shape of 8 . 7,29 In contrast, the hole effective mass is not so sensitive to the external strain; the nature of the anisotropy remains unchanged, with significantly higher effective mass in Γ-X direction than compared to Γ-Y direction. 7,29 From an application point of view, this phenomenon can be used to switch the easy direction of electronic and thermal transport in phosphorene based devices.…”
Section: Fluorination Of Phosphorenementioning
confidence: 97%